2018
DOI: 10.1080/2159676x.2018.1527781
|View full text |Cite
|
Sign up to set email alerts
|

There were other guys in the same boat as myself’: the role of homosocial environments in sustaining men’s engagement in health interventions

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law. The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The importance of shared characteristics (e.g., body type or goals) for driving group identification processes have been previously acknowledged in a similar men-only, community-based weight loss management intervention (Lozano-Sufrategui, Pringle, McKenna, & Carless, 2019). According to Lozano-Sufrategui and colleagues, participants in this program described perceptions of being in a 'shared safe place', encompassed by feelings that everybody in the program was 'in the same boat'.…”
Section: Group Identification Processesmentioning
confidence: 95%
“…The importance of shared characteristics (e.g., body type or goals) for driving group identification processes have been previously acknowledged in a similar men-only, community-based weight loss management intervention (Lozano-Sufrategui, Pringle, McKenna, & Carless, 2019). According to Lozano-Sufrategui and colleagues, participants in this program described perceptions of being in a 'shared safe place', encompassed by feelings that everybody in the program was 'in the same boat'.…”
Section: Group Identification Processesmentioning
confidence: 95%
“…Following Kokko (2016, p.82), a healthpromoting sports club is "a setting (which does not need to have physical boundaries) with sustained health promotion practices at the organization, club, and coach levels of the system". Recent evidence from northern Europe has shown that sports settings can attract groups who remain unreached in traditional healthcare (Lewis, Reeves and Roberts, 2016;Lozano-Sufrategui et al, 2018). For example, Trivedy et al (2017) suggested that cricket stadia are a feasible setting for providing health interventions for Black and Minority Ethnic (BME) groups.…”
Section: Introductionmentioning
confidence: 99%
“…Focus groups and interviews have been used previously to investigate participant experiences of attending football-led health improvement interventions reflecting both the implementation component of RE-AIM [ 37 ] and the key characteristics such as the Premier League Men’s health Evaluation and the Fit Red’s men’s health evaluation [ 32 , 52 ]. They can be an inclusive, efficient, and convenient method to capture information on participant experiences of engaging with interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to inviting participants to engage in the focus group, the researchers attended a series of social events such as the Christmas bowling event and planned CARE activities to build up rapport with potential volunteers. This approach has been adopted elsewhere in research studies investigating the impact of football-led health improvement programs [ 32 , 52 ]. This meant that on the day of the focus groups, participants recognised the researchers and that a previous connection had already been established [ 52 ] and thus contributed to building capacity for research recommended in the literature [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation